Oil-based rock debris residue lightweight high-strength building ceramsite as well as preparation method and application thereof
By combining oil bedrock debris residues with other industrial solid waste and reinforced materials, low-density, high-strength lightweight and high-strength building ceramics are prepared, which solves the problems of high density and environmental pollution after oil bedrock debris treatment, and achieves the The effects of resource utilization and environmental protection.
Patent Information
- Application Number
- CN202311008595.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to achieve lightweight high-strength ceramic granules of oil bedrock debris residues at low density, and there is still a risk of environmental pollution after treatment of oil bedrock debris.
The raw materials such as oil-bed rock debris residue, red mud, fly ash, waste quartz sand, coal gangue, silicon carbide, steel fiber and lithium carbonate were prepared through wet ball milling, dry mixing, granulation and roasting processes. Density, high strength lightweight high-strength building ceramics.
It has achieved low density and high intensity conversion of oil bedrock chip residues, and has the characteristics of environmental protection, economicality, simple technology, large chip consumption and high resource utilization, effectively solving the problem of large accumulation of oil bedrock chips.
Smart Images

Figure CN119462200A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of waste resource disposal, and particularly relates to an oil-based rock debris residue lightweight high-strength building ceramsite, and a preparation method and application thereof. Background Art
[0002] In recent years, the shortage of conventional natural gas resources and the optimization of energy structure have rapidly promoted the exploration and exploitation of shale gas. In the process of shale gas exploitation, in order to avoid the problems of hydration expansion and collapse and blockage of shale layers, oil-based drilling fluids are widely used to protect oil and gas layers, maintain hydrostatic pressure and well wall stability, and clean the bottom of the well, which also leads to the generation of a large amount of oil-based cuttings. Oil-based cuttings have complex compositions and contain a variety of organic pollutants, heavy metals and other substances that are harmful to the human body and the environment. They have been listed as hazardous wastes (National Hazardous Waste List, HW08). If untreated oil-based cuttings are discharged at will or directly landfilled, it will cause serious harm to the ecological environment, animals and plants, and even human health.
[0003] Thermal desorption technology is currently the most commonly used method for treating oil-based cuttings. However, the oil-based drilling cuttings residue formed after thermal desorption technology treatment still contains a small amount of petroleum hydrocarbons and heavy metals, which are still classified as hazardous waste. Direct discharge or landfill will cause secondary pollution to the environment and waste a lot of land resources. Therefore, it is urgent to find an environmentally friendly, economical, simple process, large cuttings consumption, and high resource utilization rate material to achieve resource processing of oil-based cuttings.
[0004] At present, it is urgent to find new building materials that are energy-saving, environmentally friendly, green and efficient. With its unique superior properties, such as light weight and high strength, thermal insulation, earthquake resistance and fire resistance, sound insulation and noise reduction, and excellent durability, ceramsite has gradually stood out in the fields of construction engineering, roadbed and pavement treatment, flower breeding, and water pollution treatment. Therefore, the development of a variety of solid wastes to synergistically treat oil-based rock debris residues to prepare lightweight and high-strength building ceramsite can achieve harmless, economical, simple process, large chip consumption, and high resource utilization of oil-based rock debris residues, and expand the road to comprehensive utilization of oil-based rock debris.
[0005] Chinese invention patent CN201910801093.0 discloses a method for producing expanded ceramsite using solid waste drilling cuttings produced by oilfield exploration and development, wherein the raw material composition includes 50-70% of the drilling cuttings of the solid waste produced by oilfield exploration and development, 30-50% of the fly ash, and 0-8% of the fine coal powder. At the same time, the raw material is added with the following composition by weight: 53-79 parts of silicon dioxide, 12-26 parts of aluminum oxide, 5-10 parts of a gas-generating component for enhancing plasticity (including one of calcium carbonate, magnesium carbonate, ferrous sulfide and carbon) and 10-15 parts of a solvent component for reducing the combustion temperature (including at least one of calcium oxide, magnesium oxide, sodium oxide and ferrous oxide). The two-stage sintering temperature is set, the first preset temperature is 1150-1250°C, and the first preset time is 23-30min. The second preset temperature is 1280-1320°C, and the second preset time is 10-20min; a kind of sintered expanded ceramsite is produced. Patent CN201611026609.1 discloses an oleophilic ceramsite using thermal analysis of oil-based drill cuttings residues. The raw material components are mainly composed of thermal analysis residues of oil-based drill cuttings, bauxite, potassium feldspar, and bentonite. The raw materials are calculated by weight as follows: 30-60 parts of thermal analysis residues of oil-based drill cuttings, 10-40 parts of bauxite, 5-20 parts of potassium feldspar, and 3-20 parts of bentonite. The raw materials also include glass powder, and the amount of glass powder added accounts for 0-20% of the total weight of other raw materials. At a sintering temperature of 1040-1260°C, the ceramsite that meets the specifications after burning is immersed in H2SO4 solution for 12-24 hours, then washed with water until neutral and dried. The purified ceramsite is then immersed in a modified solution mainly composed of an aluminate coupling agent, water, and ethanol and having a pH of 3 to 6, thereby preparing an oleophilic ceramsite of oil-based drill cuttings residue. Patent CN202110460643.4 discloses taking low-oil-content sludge, which is crushed and pre-treated to become a fine powder, mixing the crushed low-oil-content sludge and sludge residue, and then mixing with a high-temperature adhesive and water. The weight ratio of the four raw materials, sludge residue, low-oil-content sludge, high-temperature adhesive, and water, is as follows: sludge residue: ≤10%; low-oil-content sludge: 20% to 70%; high-temperature adhesive: 10% to 20%; water: ≤10%; at a firing temperature of 1000 to 1150°C and a firing time of 30 to 60 minutes, the bulk density of the prepared ceramsite is 690kg / m 3 , the water absorption rate in 1h is 5.40%, and the cylinder pressure strength is 4MPa.
[0006] In the survey against the above background, it can be found that some research has been carried out on the preparation of expanded clay from oilfield waste. However, in all the studies on the preparation of expanded clay from oilfield waste, the density grade is too high or it is difficult to meet the requirements of lightweight and high-strength expanded clay required by the specifications at a lower density level, that is, it is difficult to meet the requirements of having excellent mechanical properties at low density.
[0007] In summary, there are still various problems in the current oil-based rock cuttings residue treatment technology. How to achieve the reduction and resource utilization of oil-based rock cuttings residue disposal while obtaining a conversion product with better performance has become an urgent problem that needs to be solved. Summary of the invention
[0008] In view of the above problems, the present invention provides a lightweight high-strength building ceramsite made of oil-based rock debris residue, a preparation method and application thereof. The density grade of the lightweight high-strength building ceramsite is lower than the density of the ceramsite currently prepared using oil field waste, and its strength is higher than the requirements of the standard lightweight high-strength ceramsite with a density grade of 600. It has the characteristics of light weight, high strength, high sphericity and low water absorption. It is a new type of building material that is environmentally friendly, economical, simple in process, has a large amount of debris consumption and a high resource utilization rate, and can effectively solve the large accumulation of oil-based rock debris.
[0009] In one aspect of the present invention, there is provided an oil-based rock debris residue lightweight high-strength building ceramsite, the raw materials for its preparation include the following components in parts by weight: 50-70 parts of oil-based rock debris residue, 3-10 parts of red mud, 5-20 parts of fly ash, 10-15 parts of waste quartz sand, 5-10 parts of coal gangue, 0.6-0.7 parts of silicon carbide, 8-10 parts of steel fiber, and 4-7 parts of lithium carbonate. Preferably, 50 parts of oil-based rock debris residue, 10 parts of red mud, 20 parts of fly ash, 10 parts of waste quartz sand, 10 parts of coal gangue, 0.6 parts of silicon carbide, 10 parts of steel fiber, and 4 parts of lithium carbonate.
[0010] The second aspect of the present invention provides a method for preparing the aforementioned oil-based rock debris residue lightweight high-strength building ceramsite, comprising: S1, wet ball milling the oil-based rock debris residue, red mud, fly ash, waste quartz sand and coal gangue, drying and crushing to obtain ceramsite raw material powder; S2, blending the remaining raw materials with the ceramsite raw material powder, adding water to adjust the moisture and then granulating to obtain green balls; S3, roasting and cooling the green balls to obtain the aforementioned oil-based rock debris residue lightweight high-strength building ceramsite.
[0011] As a specific embodiment of the present invention, in step S1, the material-water-ball ratio of the wet ball milling is 1:1:8, and the ball milling time is 2 to 4 hours; drying to constant weight at a temperature of 105±5°C; and crushing to pass through a 100-mesh sieve.
[0012] As a specific embodiment of the present invention, in step S2, the remaining raw materials and ceramsite raw material powder are dry-mixed in a intensive mixer, part of the obtained dry powder is added with water to adjust the moisture and then granulated to obtain material balls with a certain particle size, the material balls and the remaining dry powder are mixed in a rolling device to obtain material balls with increased particle size, and after drying, green balls are obtained; preferably, the rotor speed of the intensive mixer is 150 rad / min, the barrel speed is 25 rad / min, and the dry mixing time is 5 min; preferably, the rolling device is a sugar coating machine; preferably, material balls with a particle size of 8 mm are prepared first, and then material balls with a particle size of 12 mm are prepared; preferably, dried to constant weight at a temperature of 105±5°C.
[0013] As a specific embodiment of the present invention, in step S3, the material is placed in a muffle furnace for gradient calcination; preferably, the sintering system is: starting from room temperature, heating at a rate of 10°C / min to 400°C, keeping warm for 15 to 20 minutes, then keeping the heating rate unchanged and continuing to heat to 800°C, and then heating from 800°C to 1080 to 1140°C at a rate of 5°C / min, and keeping warm for 10 to 30 minutes.
[0014] As a specific embodiment of the present invention, in step S3, the cooling method is: slowly cooling to 1000°C at a cooling rate of 1-3°C / min, and then cooling to room temperature in the furnace.
[0015] The third aspect of the present invention provides a lightweight building material, which contains the aforementioned oil-based rock debris residue lightweight high-strength building ceramsite.
[0016] A fourth aspect of the present invention provides the use of the aforementioned oil-based rock debris residue lightweight high-strength building ceramsite in the harmless treatment of oil-based rock debris residue.
[0017] The fifth aspect of the present invention provides the use of the aforementioned oil-based rock debris residue lightweight high-strength building ceramsite in the production of green ecological and environmentally friendly building materials.
[0018] The lightweight high-strength building ceramsite provided by the present invention has a high content of oil-based rock debris residue in its preparation raw materials, and the total amount of industrial solid waste accounts for 100%, with a high solid waste utilization rate, and components including steel fiber, silicon carbide and lithium carbonate are specially added, wherein: 1) in addition to playing a physical reinforcement role by resisting the external stress of the ceramsite and preventing the diffusion of cracks, the steel fiber can also be used as a high-temperature auxiliary heat material due to its excellent thermal conductivity, thereby reducing the temperature gradient effect generated when the ceramsite is roasted in an electric resistance furnace, resulting in uneven temperature distribution inside the ceramsite; 2) silicon carbide and lithium carbonate are used as high-temperature synergistic foaming agents to regulate the pore size of the lightweight high-strength ceramsite matrix, while enhancing the performance of the lightweight high-strength building ceramsite. Specifically, at a temperature of 900 In the range of 1000-1100℃, as the temperature rises, a large amount of metal oxides in the mixed components accelerate the oxidation of silicon carbide, so that silicon carbide generates CO and CO2 under high temperature conditions, and micropores are generated in the ceramsite matrix; at a temperature of 1000-1200℃, the added lithium carbonate will decompose to form Li2O and CO2. At this time, a large amount of CO2 is generated and the liquid phase viscosity is reduced, so that the small pores inside the ceramsite begin to merge due to the large number, forming uniform holes with larger particle sizes, further reducing the density of the ceramsite, that is, the addition of silicon carbide is conducive to the generation of micropores in the ceramsite matrix, and the decomposition of lithium carbonate can form larger pores in the ceramsite matrix; at the same time, lithium carbonate can also be used as a nucleation agent to chemically enhance the ceramsite matrix. Specifically, due to the Li + Radius smaller than Ba 2+ radius, during the high temperature calcination stage of ceramsite, it can replace Ba in hexagonal barium feldspar 2+ , generating oxygen vacancies, leading to the breaking of Ba-O bonds, Al-O bonds, and Si-O bonds in hexagonal barium feldspar, so that the tetrahedral structure of barium feldspar is reconnected to form a three-dimensional framework structure, and the transformation of hexagonal barium feldspar to monoclinic barium feldspar is promoted. The presence of monoclinic barium feldspar can make the ceramsite matrix have good oxidation resistance, high temperature stability, alkali corrosion resistance, and mechanical properties, and monoclinic barium feldspar and a variety of aluminosilicate mineral phases have good thermal matching and chemical compatibility. At the same time, during the high-temperature firing stage of ceramsite, it is conducive to the firing of lightweight and high-strength building ceramsite; 3) Using industrial solid waste fly ash, waste quartz sand, red mud, and coal gangue, and targeting the mineral components of oil-based rock debris residues, batching technology can be used to fire a new type of lightweight and high-strength ceramsite with monoclinic barium feldspar, quartz, and hematite as the main crystal phases, realizing the preparation of all-solid waste-based lightweight and high-strength ceramsite.
[0019] The preparation method provided by the present invention comprises the following steps: 1) a powerful mixer is used to combine with a sugar coating machine to granulate. The method firstly uses a powerful mixer to grind and refine the raw materials to improve the potential activity, and then performs nucleation of ceramsite green balls to ensure that the green balls have uniform quality, high sphericity, and high balling efficiency. The green balls are then put into a sugar coating machine for rolling to adjust the particle size of the green balls and polish the green balls. The green balls prepared by the method have the characteristics of high quality, high sphericity, high balling rate, and adjustable particle size. 2) for the ceramsite in a high temperature state after the roasting is completed, the method of heat preservation and slow cooling is first adopted, with a cooling rate of 1 to 3°C / min. After the temperature drops to 1000°C, the temperature is cooled to room temperature by furnace cooling. The reason is that in the high temperature stage, the viscosity of the high temperature liquid phase increases sharply with the decrease of temperature. The method of heat preservation and slow cooling is conducive to maintaining the viscosity of the high temperature liquid phase inside the ceramsite, thereby maintaining its good internal pore structure. At the same time, heat preservation and slow cooling can improve the crystallinity of the internal crystalline phase of ceramsite, reduce the formation of glass phase, and is beneficial to the development of the internal crystal structure of ceramsite; 3) The preparation cost is low, and the bulk density of the prepared ceramsite is ≤500kg / m 3 , strength ≥4MPa, its bulk density is much lower than the bulk density of expanded clay prepared by existing technology, and its cylinder pressure strength is higher than the 600 density grade requirement of lightweight high-strength expanded clay in GB / T17431.1-2010 "Light aggregate and its test method Part 1: Light aggregate".
[0020] The beneficial effects of the present invention are:
[0021] The ceramsite of the present invention has the characteristics of light weight, high strength, high sphericity and low water absorption, and its bulk density is lower than the 600 density grade required for light high strength ceramsite in GB / T17431.1-2010 "Light Aggregate and Its Test Method Part 1: Light Aggregate", and its cylinder pressure strength reaches the requirement of 600 density grade for light high strength ceramsite. It is a new building material with environmental protection, economy, simple process, large chip consumption and high resource utilization rate, which can effectively solve the problem of large accumulation of oil-based rock chips. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a process flow chart of preparing lightweight and high-strength building ceramsite in Example 1;
[0023] Figure 2 is the XRD pattern of Examples 1 to 5;
[0024] Figure 3 These are SEM images of Examples 1 to 5, wherein: a: ceramsite sample; b: Example 1; c: Example 2; d: Example 3; e: Example 4; f: Example 5. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] A light and high-strength building ceramsite made of oil-based rock debris residues. The raw materials for its preparation are calculated by weight (in dry state) as follows: 50 parts of oil-based rock debris residues, 10 parts of red mud, 20 parts of fly ash, 10 parts of waste quartz sand, 10 parts of coal gangue, 0.6 parts of silicon carbide, 10 parts of steel fiber, and 4 parts of lithium carbonate.
[0028] The specific preparation steps are as follows:
[0029] a. Grinding: Weigh the dried oil-based rock debris, red mud, waste quartz sand, fly ash and coal gangue powder in proportion, add them into a planetary ball mill and mix them for wet grinding for 24 hours. The mass ratio of corundum balls, mixed materials and water in the ball mill is 8:1:1. Let the ground slurry stand for 3 hours, filter out the supernatant and dry it in a forced air drying oven (105±5℃) to constant weight. Finally, use a tissue crusher to crush it and pass it through a 100-mesh sieve to obtain ceramsite raw material powder.
[0030] b. Dry mixing of raw materials: Put steel fiber, silicon carbide, lithium carbonate powder and ceramsite raw material powder into a high-pressure mixer for material mixing. Adjust the speed of the rotor and barrel inside the high-pressure mixer to 150rad / min and 25rad / min respectively. Mix for 5 minutes to obtain dry powder.
[0031] c. Granulation with a powerful mixer and a sugar coating machine: After the dry mixing of the powerful mixer is completed, keep the speed of the barrel unchanged, quickly adjust the speed of the rotor inside the powerful mixer to 1000rad / min, and use a watering can to evenly spray 17 parts of water on the high-speed stirring material through the water inlet of the powerful mixer to ensure the uniformity of the particle size of the spheres. After obtaining the green body with a particle size of 8mm, the powerful mixer stops working. The prepared 8mm green body balls are put into the sugar coating machine and rolled, and an appropriate amount of reserved dry powder is added during the process to obtain green body balls with a particle size of 12mm. Finally, the 12mm green body balls are placed in a blast drying oven (105±5℃) and dried to constant weight.
[0032] d. Calcination: The prepared raw material balls are placed in a muffle furnace for calcination. The sintering system is as follows: starting from room temperature, the temperature is increased to 400°C at a rate of 10°C / min, kept at this temperature for 15 minutes, and then the temperature is increased to 800°C at a rate of 10°C / min, and then the temperature is increased from 800°C to 1140°C at a rate of 5°C / min, and kept at this temperature for 20 minutes.
[0033] e. Cooling: After the calcination, the ceramsite in a high temperature state is cooled by a step-by-step cooling method, from 1140℃ to 1000℃ in a heat preservation and slow cooling manner, with a cooling rate of 1℃ / min. After the temperature drops to 1000℃, it is cooled to room temperature by furnace cooling.
[0034] f. Performance evaluation: After taking out the expanded clay product, test its cylinder pressure strength, bulk density and water absorption rate.
[0035] Example 2
[0036] A light and high-strength building ceramsite made of oil-based rock debris residues. The raw materials for its preparation are calculated by weight (in dry state) as follows: 60 parts of oil-based rock debris residues, 10 parts of red mud, 10 parts of fly ash, 10 parts of waste quartz sand, 10 parts of coal gangue, 0.7 parts of silicon carbide, 8 parts of steel fiber, and 4 parts of lithium carbonate.
[0037] The specific preparation steps are the same as those in Example 1, except that the sintering temperature is 1120°C.
[0038] Example 3
[0039] A light and high-strength building ceramsite made of oil-based rock debris residues. The raw materials for its preparation are calculated by weight (in dry state) as follows: 65 parts of oil-based rock debris residues, 10 parts of red mud, 10 parts of fly ash, 10 parts of waste quartz sand, 5 parts of coal gangue, 0.6 parts of silicon carbide, 10 parts of steel fiber, and 5 parts of lithium carbonate.
[0040] The specific preparation steps are the same as those in Example 1, except that the sintering temperature is 1110°C.
[0041] Example 4
[0042] A light and high-strength building ceramsite made of oil-based rock debris residues. The raw materials for its preparation are calculated by weight (in dry state) as follows: 67 parts of oil-based rock debris residues, 3 parts of red mud, 10 parts of fly ash, 15 parts of waste quartz sand, 5 parts of coal gangue, 0.6 parts of silicon carbide, 10 parts of steel fiber, and 7 parts of lithium carbonate.
[0043] The specific preparation steps are the same as those in Example 1, except that the sintering temperature is 1080°C.
[0044] Example 5
[0045] A light and high-strength building ceramsite made of oil-based rock debris residues. The raw materials for its preparation are calculated by weight (in dry state) as follows: 70 parts of oil-based rock debris residues, 5 parts of red mud, 5 parts of fly ash, 15 parts of waste quartz sand, 5 parts of coal gangue, 0.6 parts of silicon carbide, 10 parts of steel fiber, and 6 parts of lithium carbonate.
[0046] The specific preparation steps are the same as those in Example 1, except that the sintering temperature is 1110°C.
[0047] Test example
[0048] 1. Referring to GB / T17431.2-2010 "Light Aggregate and Its Test Method Part 2: Light Aggregate Test Method", the cylinder compressive strength, bulk density and water absorption of the lightweight high-strength ceramsite prepared in the above embodiments were tested, and the results are as follows:
[0049] Table 1 Test results of various embodiments
[0050]
[0051] 2. XRD and SEM tests were performed on the lightweight and high-strength ceramsite prepared in the above embodiments. The XRD results are as follows: Figure 2 As shown in FIG. 1 , it can be seen from the XRD spectrum that the light and high-strength ceramsite with monoclinic celsium feldspar, quartz and hematite as the main crystal phases is obtained by firing the present invention; the SEM results are shown in FIG. Figure 3 As shown, it can be seen from the SEM picture that the ceramsite prepared by the present invention has high sphericity and uniform pores with larger particle sizes are generated inside.
[0052] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A lightweight and high-strength building ceramsite made of oil-based rock debris residue, characterized in that: The raw materials for its preparation include the following components in parts by weight: 50-70 parts of oil-based rock debris residue, 3-10 parts of red mud, 5-20 parts of fly ash, 10-15 parts of waste quartz sand, 5-10 parts of coal gangue, 0.6-0.7 parts of silicon carbide, 8-10 parts of steel fiber, and 4-7 parts of lithium carbonate.
2. The oil-based rock debris residue lightweight high-strength building ceramsite according to claim 1, characterized in that: The raw materials for its preparation include the following components in parts by weight: 50 parts of oil-based rock debris residue, 10 parts of red mud, 20 parts of fly ash, 10 parts of waste quartz sand, 10 parts of coal gangue, 0.6 parts of silicon carbide, 10 parts of steel fiber, and 4 parts of lithium carbonate.
3. The method for preparing the oil-based rock debris residue lightweight high-strength building ceramsite according to claim 1 or 2, characterized in that: The preparation method comprises: S1, wet-milling the oil-based rock debris, red mud, fly ash, waste quartz sand and coal gangue, drying and crushing them to obtain ceramsite raw material powder; S2, blending the remaining raw materials with ceramsite raw material powder, adding water to adjust the humidity and then granulating to obtain green balls; S3, after the green ball is roasted and cooled, the oil-based rock debris residue lightweight high-strength building ceramsite is obtained.
4. The method for preparing light and high-strength building ceramsite from oil-based rock debris residue according to claim 3, characterized in that: In step S1, the material-water-ball ratio of the wet ball milling is 1:1:8, and the ball milling time is 2 to 4 hours; drying to constant weight at a temperature of 105±5° C.; and crushing to pass through a 100-mesh sieve.
5. The method for preparing light-weight and high-strength building ceramsite from oil-based rock debris residue according to claim 3, characterized in that: In step S2, the remaining raw materials and ceramsite raw material powder are dry-mixed in a strong mixer, a portion of the obtained dry powder is added with water for moisture adjustment and then granulated to obtain material balls with a certain particle size, the material balls and the remaining dry powder are mixed in a rolling device to obtain material balls with increased particle size, and after drying, green balls are obtained; Preferably, the rotor speed of the intensive mixer is 150 rad / min, the barrel speed is 25 rad / min, and the dry mixing time is 5 min; Preferably, the rolling device is a sugar coating machine; Preferably, the pellets with a particle size of 8 mm are prepared first, and then the pellets with a particle size of 12 mm are prepared; Preferably, the mixture is dried at 105±5°C to a constant weight.
6. The method for preparing light-weight and high-strength building ceramsite from oil-based rock debris residue according to claim 3, characterized in that: In step S3, the material is placed in a muffle furnace for gradient calcination; preferably, the sintering system is: starting from room temperature, heating at a rate of 10°C / min to 400°C, keeping warm for 15 to 20 minutes, then keeping the heating rate constant and continuing to heat to 800°C, then heating from 800°C to 1080 to 1140°C at a rate of 5°C / min, and keeping warm for 10 to 30 minutes.
7. The method for preparing light-weight and high-strength building ceramsite from oil-based rock debris residue according to claim 3, characterized in that: In step S3, the cooling method is: slowly cooling to 1000°C at a cooling rate of 1-3°C / min, and then cooling to room temperature in the furnace.
8. A lightweight building material, characterized in that: The lightweight building material contains the oil-based rock debris residue lightweight high-strength building ceramsite according to claim 1 or 2.
9. Use of the lightweight high-strength building ceramsite of oil-based rock debris residue as described in claim 1 or 2 in the harmless treatment of oil-based rock debris residue.
10. Use of the oil-based rock debris residue lightweight high-strength building ceramsite according to claim 1 or 2 in the production of green ecological and environmentally friendly building materials.
Citation Information
Patent Citations
Method for preparing high-strength ceramsite from oil sludge
CN112919879A
Oleophylic ceramsite adopting oil-based drilling cutting residues obtained after thermal decomposition and preparation method of oleophylic ceramsite
CN106518147A
Ceramisite fracturing sand with oleophylic characteristic and preparation method thereof
CN106747371A
Concrete lightweight aggregate and preparation method thereof
CN107601936A
Method for producing ceramsite by using well drilling rock debris generated during oilfield exploitation and development
CN110407586A